2023
DOI: 10.1186/s13046-022-02586-w
|View full text |Cite|
|
Sign up to set email alerts
|

Helicobacter pylori-induced NAT10 stabilizes MDM2 mRNA via RNA acetylation to facilitate gastric cancer progression

Abstract: Background N4-acetylcytidine (ac4C), a widespread modification in human mRNAs that is catalyzed by the N-acetyltransferase 10 (NAT10) enzyme, plays an important role in promoting mRNA stability and translation. However, the biological functions and regulatory mechanisms of NAT10-mediated ac4C were poorly defined. Methods ac4C mRNA modification status and NAT10 expression levels were analyzed in gastric cancer (GC) samples and compared with the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Notably, when cells were cultured with an inhibitor of NAT10, Remodelin (10 μM), 10,38,39 which has been applied to inhibit ac 4 C modification in vitro and vivo, 40,41 the Remodelin not only inhibited NAT10 but also increased sensitivity to cisplatin in bladder cancer and mouse xenografts. 41 As shown in Figure 3B, after cell treatment with the addition of Remodelin for 24 h, the Fac 4 C modification on RNA was notably weakened.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notably, when cells were cultured with an inhibitor of NAT10, Remodelin (10 μM), 10,38,39 which has been applied to inhibit ac 4 C modification in vitro and vivo, 40,41 the Remodelin not only inhibited NAT10 but also increased sensitivity to cisplatin in bladder cancer and mouse xenografts. 41 As shown in Figure 3B, after cell treatment with the addition of Remodelin for 24 h, the Fac 4 C modification on RNA was notably weakened.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although it is an essential protein, data indicates NAT10 may be a viable therapeutic target for the treatment of various cancers and cellular aging, and has been implicated in the regulation of p53 17,[29][30][31][32][33][34][35] , as well as the human accelerated aging genetic disorder, Hutchinson-Gilford Progeria Syndrome (HGPS) 36,37 . Heterozygous knockout of NAT10 has been demonstrated to modulate HGPS phenotypes in a mouse model 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Deng et al [ 78 ] studied the relationship between ac4C modification and GC occurrence and found that NAT10 is significantly up-regulated in GC cells versus healthy cells. H. pylori infection contributes to NAT10 induction, regulating p53 stability via MDM2 proto-oncogene (MDM2).…”
Section: Introductionmentioning
confidence: 99%